The role of Golgi complex proteins in cell division and consequences of their dysregulation - Iannitti, Roberta; Mascanzoni, Fabiola; Colanzi, Antonino; Spano, Daniela (Frontiers in Cell and Developmental Biology, 2025)
The GC (Golgi complex) plays a pivotal role in the trafficking and sorting of proteins and lipids until they reach their final destination. Additionally, the GC acts as a signalling hub to regulate a multitude of cellular processes, including cell polarity, motility, apoptosis, DNA repair and cell division. In light of these crucial roles, the GC has garnered increasing attention, particularly given the evidence that a dysregulation of GC-regulated signalling pathways may contribute to the onset of various pathological conditions. This review examines the functions of the GC and GC-localised proteins in regulating cell cycle progression, in both mitosis and meiosis. It reviews the involvement of GC-resident proteins in the formation and orientation of the spindle during cell division. In light of the roles played by the GC in controlling cell division, this review also addresses the involvement of the GC in cancer development. Furthermore, TCGA (The Cancer Genome Atlas) database has been queried in order to retrieve information on the genetic alterations and the correlation between the expression of GC-localised proteins and the survival of cancer patients. The data presented in this review highlight the relevance of the GC in regulating cell cycle progression, cellular differentiation and tumourigenesis.